KONSEP SYAJAROTUL MIRATS DALAM PRAKTEK KEWARISAN ISLAM - Ritonga, Raja; Akhyar, Akhyar; Tambunan, Jannus; Muda, Andri (SAMAWA, 2022)
Abstrac The practice of Islamic inheritance is an absolute thing that applies to every event of death. However, its implementation is less massive in the community. So it appears a fact that the practice of Islamic inheritance is directly proportional to the understanding of the community regarding the science of faraid. Some approaches are taken to understand Islamic inheritance theory comprehensively so that it can be practiced properly and correctly. This study will describe the systematics of Islamic inheritance through the concept of syajarotul mirats. The method used in this study is a qualitative method with the type of library research. In collecting data, researchers searched for many books and other scientific works in the form of journals that have relevance to the research theme. Furthermore, the data were analyzed using content analysis. As a result, the research explains that the concept of syajarotul mirats can map the position of each heir based on the line of kinship to the heir. In addition, this concept can also describe the parts of each heir in detail.